assignFAST: An Autosuggest-Based Tool for FAST Subject Assignment. - Bennett, Rick; O'Neill, Edward T.; Kammerer, Kerre (Information Technology & Libraries, 2014)
Subject assignment is really a three-phase task. The first phase is intellectual--reviewing the material and determining its topic. The second phase is more mechanical--identifying the correct subject heading(s). The final phase is retyping or cutting and pasting the heading(s) into the cataloging interface along with any diacritics, and potentially correcting formatting and subfield coding. If authority control is available in the interface, some of these tasks may be automated or partially automated. A cataloger with a reasonable knowledge of Faceted Application of Subject Terminology (FAST)1,2 or even Library of Congress Subject Headings (LCSH)3 can quickly get to the proper heading but usually needs to confirm the final details--was it plural? am I thinking of an alternate form? is it inverted? etc. This often requires consulting the full authority file interface. assignFAST is a web service that consolidates the entire second phase of the manual process of subject assignment for FAST subjects into a single step based on autosuggest technology.